News writing and reporting for today's media - Itule, Bruce D. (McGraw-Hill, 2003)
"News Writing and Reporting" takes students on the beat, into the press box, council chambers, courthouse, and to a speech and press conference. It introduces them to current issues such as cultural sensitivity and legal and ethical considerations, and to reporters and editors who offer their down-to-earth advice. Whenever possible, professional journalists covering actual stories are used as instructional models. Students are exposed to the work of professionals while gathering the tools to follow in their footsteps.